Erratum Jurnal Psikologi Volume 48, Number 2 in August 2021 - Erratum Jurnal Psikologi (Faculty of Psychology, Universitas Gadjah Mada, 2021)
This erratum is to explain a pagination error occurred in the published issue of Jurnal Psikologi Volume 48, Number 2 in August 2021. The error was related to the numbering system given to the first page of the Issue that duplicates the previous issue Volume 48, Number 1. The error only applies on the PDF files of the articles, but the metadata remains the correct page.